Elaeocarpusin Inhibits Mast Cell-Mediated Allergic Inflammation - Kim, Min-Jong; Kim, Yeon-Yong; Choi, Young-Ae; Baek, Moon-Chang; Lee, Byungheon; Park, Pil-Hoon; Shin, Tae-Yong; Kwon, Taeg Kyu; Khang, Dongwoo; Kim, Sang-Hyun (Frontiers in Pharmacology, 2018)
Mast cells are major effector cells for allergic responses that act by releasing inflammatory mediators, such as histamine and pro-inflammatory cytokines. Accordingly, different strategies have been pursued to develop anti-allergic and anti-inflammatory candidates by regulating the function of mast cells. The purpose of this study was to determine the effectiveness of elaeocarpusin (EL) on mast cell-mediated allergic inflammation. We isolated EL from Elaeocarpus sylvestris L. (Elaeocarpaceae), which is known to possess anti-inflammatory properties. For this study, various sources of mast cells and mouse anaphylaxis models were used. EL suppressed the induction of markers for mast cell degranulation, such as histamine and beta-hexosaminidase, by reducing intracellular calcium levels. Expression of pro-inflammatory cytokines, such as tumor necrosis factor-α and IL-4, was significantly decreased in activated mast cells by EL. This inhibitory effect was related to inhibition of the phosphorylation of Fyn, Lyn, Syk, and Akt, and the nuclear translocation of nuclear factor-kappaB. To confirm the effect of EL in vivo, immunoglobulin E-mediated passive cutaneous anaphylaxis (PCA) and ovalbumin-induced active systemic anaphylaxis (ASA) models were induced. EL reduced the PCA reaction in a dose dependent manner. In addition, EL attenuated ASA reactions such as hypothemia, histamine release, and IgE production. Our results suggest that EL is a potential therapeutic candidate for allergic inflammatory diseases that acts via the inhibition of mast cell degranulation and expression of proinflammatory cytokines.